RANCANG BANGUN MESIN PENCUCI UMBI PORANG UNTUK MENINGKATKAN KINERJA PENGOLAHAN PORANG - Suharto Suharto; Suryanto Suryanto; Sarana Sarana; Teguh Budi Santosa (Jurnal Teknologi Terapan, 2018)
Porang  (Amorphophallus Oncophyllus) has long been known to the public, especially in the Magelang region. Porang contain very high glucomannan. Glucomannan is a water soluble fiber that is strong and low caloric hydrocolloid which is widely used food industry (noodle, tofu / konyaku, meatball, jely, artificial rice) and non food (cosmetics, capsules). Semarang State Polytechnic Hi-link Program in cooperation with the Magelang City Agriculture Office covers the cultivation, processing, and utilization of porang. Processing starts from tuber harvest, washed, chopped, dried, dipped. The washing process was initially done manually and simply with a brush and water spray so that the laundry was less clean and long-time. The purpose of this research is to design a porang bulb washer with motor gasoline drive to improve clean washing result and number of porang bulbs. The method used approach with of R & D (research & development) is to describe the current condition (exsiting), analyzing deficiencies, and improve performance for the better. Design stage starts from designing, manufacturing, and performance testing. The results obtained were porang washing machine driven by gasoline engine with power 10 HP, length dimension 1800 (mm), width 1200 (mm), and height 1200 (mm). The result of clean washing test with brush length 35 (cm), rotation of rotor 50 (rpm) and washing capacity of porang 1400 (kg / hour). The capacity of washing porang  1400 (kg / hour) is greater than washing manually, and the washing results are clean than more.